ANALYZING THE DISTRIBUTION OF POLLUTANTS IN URBAN LANDSCAPES (American Journal of Technology and Applied Sciences, 2023)
Environmental quality control is one of the most important functions of environmental protection, as it is aimed at creating reliable information for planning and implementing effective environmental protection measures. Researching environmental monitoring is associated with problems such as large-scale analytical work, large financial costs, imperfect methodological support for environmental situation assessment, multidimensional data bank processing, and others.